The Synergistic Effects of Combined Use of Mentha longifolia, Thymus carmanicus, and Trachyspermum copticum on Growth Performance, Feed Utilization, and Expression of Key Immune Genes in Rainbow Trout (Oncorhynchus mykiss) - Raissy, Mehdi; Ahmadi Kabootarkhani, Mehdi; Sanisales, Kimia; Mohammadi, Mohammad; Rashidian, Ghasem (Frontiers in Veterinary Science, 2022)
Medicinal plants exhibit remarkable positive effects on different aspects of fish physiology. This study aimed to evaluate the possible impact of a combination of plants (Mentha longifolia, Thymus carmanicus, and Trachyspermum copticum) on growth performance, immune responses and key immune gene expression of rainbow trout. For this purpose, four diets were designed, including zero, 0.25, 0.5, and 1% of a mixture of plants per kg of diet, representing dietary treatments of control, T1, T2, and T3, respectively. Two hundred forty fish (weighing 23.11 ± 0.57 g) were fed 3% of body weight twice a day for 45 days. The results showed that growth parameters of weight gain (except for T1) and FCR were significantly improved in fish receiving all levels of plants, with T3 showing the best growth results. Digestive enzymes activities were notably increased in T1 and T2 compared to the control. Stress biomarkers (glucose and cortisol) were significantly decreased in T1 and T2, while T3 was not significantly different from the control. Immunological responses were significantly improved in T2, while T1 andT3 did not show a statistical difference in terms of lysozyme activity. Catalase activity was noticeably decreased in T1, although superoxide dismutase and malondialdehyde were highest in T2. Immune-related genes were significantly up-regulated in T3 compared to other treatments. Also, antioxidant enzyme coding genes were strongly up-regulated in T2 and T3. Overall, the present results suggest that 1% inclusion of the mixture of M. longifolia, T. carmanicus, and T. copticum (T2) can be used to improve the growth and immunity of rainbow trout.